(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The aim of this research is to identify the extent to which the Conventional and Islamic banks are committed to implement the requirements of the corporate governance in its financial reports. In addition to its commitment to transparency and clarity in dealing with the shareholders and stockholders to protect their interests and to determine the impact of the commitment of the corporate governance on assessing the financial performance of the conventional and Islamic banks that participate in Bahrain Stock Exchange.